PEMBERIAN PIDANA TAMBAHAN TERHADAP PENCABUTAN HAK-HAK POLITIK TERPIDANA KASUS KORUPSI BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Mohd. Yusuf D.M.,; Elvi Sukesih,; Devi Susanti,; Hifni Soba, (The Juris, 2022)
Where the meaning of equal opportunity in government is inseparable from political rights which implies political rights or political rights is a right which is to take part and play a role in a form of government that exists in a country. So that in terms of civil and political rights for every Indonesian citizen, the implementation is very clearly regulated in the 1945 Constitution of the Republic of Indonesia, Chapter XA of Human Rights Articles 28A to Article 28J, while the explanation of political rights for citizens is regulated in Article 26D paragraph (3) states that every citizen has the right to obtain equal opportunities in government. The formulation of the problem in this study is how to revoke the political rights of convicts of corruption cases based on laws and regulations, how to grant additional criminal rights to the revocation of political rights of convicts of corruption cases based on laws and regulations. The method used is normative legal research. Based on the results of the study it is known that the Revocation of the Political Rights of Convicted Corruption Cases Based on Legislation that Based on these provisions the additional criminal imposition of revocation of political rights against convicts is not contrary to the Criminal Code as long as the revocation of rights is accompanied by a period of application. The right to vote and be elected to public office can be classified as the right to freedom of thought and conscience. Human rights are rooted in the human person because of their humanity, if they are revoked then their humanity will also be lost.